IMF Survey, Volume 30, Issue 11. (IMF Survey; IMF Survey ;, 2001)
The Web edition of the IMF Survey is updated several times a week, and contains a wealth of articles about topical policy and economic issues in the news. Access the latest IMF research, read interviews, and listen to podcasts given by top IMF economists on important issues in the global economy. www.imf.org/external/pubs/ft/survey/so/home.aspx.